Plataforma para medição de forças na região plantar de pacientes normais e hemiplégicos - Assunção-Sanches, M. A. [UNESP]; Urban, M. Fernandes Réu [UNESP]; Estremote, M. Márcio [UNESP]; Pontes, Wesley [UNESP]; Dos Santos, E. Alteris [UNESP]; De Freitas, R. L. Barros [UNESP]; De Carvalho, A. Cesinando [UNESP]; De Carvalho, A. A. [UNESP] (Springer Nature, 2013)
This work describes an electronic system implementation with two force plates, 24 load cells with strain gages, signal conditioning circuit, interfacing circuit and data acquisition system, designed for measuring plantar force distribution in patients. The system presented linear response, low hysteresis, with determination coefficient of 0.9997, precision better than 0,84% and resolution less than 0.5 N. The Measurements are presented on a computer screen and easier visualization to specialists, mainly physicians, physiotherapists and occupational therapists. Using the system, the distribution of weight in the plantar region of 100 normal subjects and 10 hemiplegic patients was investigated. There were determined the relationship between weight distribution on the right and left forefoot, hemiplegic patients and normal patients, with the implemented system. © 2013 Springer.
Keywords: Computer screens; Data acquisition system; Determination coefficients; Electronic systems; Force distributions; Hemiplegic patients; Interfacing circuits; Weight distributions; Signal conditioning circuits; Biomedical engineering